2015
DOI: 10.1515/prilozi-2015-0073
|View full text |Cite
|
Sign up to set email alerts
|

Steroid Resistant Nephrotic Syndrome-Genetic Consideration

Abstract: Nephrotic syndrome is defined as the association of massive proteinuria, hypoalbuminaemia, edema, and hyperlipidemia. It is separated to steroid-sensitive or steroid-resistant (SRNS) forms in respect to the response to intensive steroid therapy. SRNS usually progresses to end-stage renal failure. According to the North American Pediatric Renal Trials and Collaborative Studies SRNS constitutes the second most frequent cause of ESRD in the first two decades of life. Unfortunately, there is no curative treatment … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
22
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(22 citation statements)
references
References 29 publications
0
22
0
Order By: Relevance
“…For example, variants in the NPHS2 gene should avoid steroid and immunosuppressive agents, and renal transplantation is the suitable choice for these patients; patients with ADCK4 or CUBN variants may be amenable to supplementation with coenzyme Q10 or vitamin B12 [10]; patients with recessive variants in PLCE1 may respond fully to the treatment with steroids or cyclosporine A (CsA) [1]; and patients with a WT1 mutation may respond to CsA and methylprednisolone pulses [4]. However, Buscher et al showed that only 3% of patients with genetic SRNS experienced a complete remission and 16% of patients with genetic SRNS experienced a partial remission after CsA therapy [34].…”
Section: Patient Treatment Of Genetic Srnsmentioning
confidence: 99%
See 1 more Smart Citation
“…For example, variants in the NPHS2 gene should avoid steroid and immunosuppressive agents, and renal transplantation is the suitable choice for these patients; patients with ADCK4 or CUBN variants may be amenable to supplementation with coenzyme Q10 or vitamin B12 [10]; patients with recessive variants in PLCE1 may respond fully to the treatment with steroids or cyclosporine A (CsA) [1]; and patients with a WT1 mutation may respond to CsA and methylprednisolone pulses [4]. However, Buscher et al showed that only 3% of patients with genetic SRNS experienced a complete remission and 16% of patients with genetic SRNS experienced a partial remission after CsA therapy [34].…”
Section: Patient Treatment Of Genetic Srnsmentioning
confidence: 99%
“…Idiopathic nephrotic syndrome (INS) is one of the most common renal diseases in the pediatric population, which is characterized by massive proteinuria, hypoalbuminemia, edema, and hyperlipidemia [1]. About 10-20% of affected children have steroid-resistant nephrotic syndrome (SRNS) and do not respond well to steroid therapy [2,3].…”
Section: Introductionmentioning
confidence: 99%
“…( 0.058, 0.671,_) ( Table.3) . NPHS2 mutations have been reported as the most common cause of childhood onset in autosomal recessive SRNS (Sadowski et al 2015;Guaragna et al 2015;Tasic et al 2015). The most frequent renal histological feature Associated with SRNS is focal segmental glomerulosclerosis (FSGS) (Joshi et al 2013;Liu and Wang 2017).…”
Section: Whole Exome Sequencing (Wes)mentioning
confidence: 99%
“…Patients in whom proteinuria does not stop after about one month are classified as resistant which describe as steroid resistant nephrotic syndrome(SRNS) (Mekahli et al 2009). SRNS is considered as a poor prognostic disease, in which 30-40% of it progresses to end stage renal disease(ESRD), requiring dialysis and transplantation (Tasic et al 2015). The most frequent renal histological feature associated with SRNS is focal segmental glomerulosclerosis (FSGS).…”
Section: Introductionmentioning
confidence: 99%
“…Steroid-resistant nephrotic syndrome (SRNS) is a challenging clinical task since it has heterogeneous etiology and extremely variable clinical outcomes (1). The prevalence of SRNS is 15% in children and 40% in adults (2). Renal histology in most of SRNS cases displays the presence of focal segmental glomerulosclerosis (FSGS), proliferative glomerulonephritis, and minimal change disease (MCD) (2,3).…”
Section: Introductionmentioning
confidence: 99%